Heavy Metals Impact: Adverse Impact of Heavy Metals on Bone Cells and Bone Metabolism Dependently and Independently through Anemia (Adv. Sci. 19/2020). Issue 19 (7th October 2020) - Zhang, Shuping; Sun, Li; Zhang, Jie; Liu, Sijin; Han, Jinxiang; Liu, Yajun
Abstract : In article number 2000383, Jinxiang Han, Yajun Liu, and co‐workers review how heavy metals induce bone damages through anemia‐independent and ‐related routes. Anemia‐independent routes include bone cell dysregulation, bone formation inhibition and bone degradation enhancement, and Ca/P homeostasis disruption. Stress erythropoiesis, erythropoietin deficiency, and disordered iron homeostasis are involved in anemia‐related routes.